Asas Keseimbangan dalam Pelaksanaan Perjanjian Anjak Piutang (Factoring) - Dewi Astutty Mochtar (University of Merdeka Malang, 2019)
The principle of equilibrium contains a hope of achieving equilibrium included in an agreement or business contract, where the interests of the individual are guaranteed by objective law, in carrying out the agreement there must be a balance of rights and obligations of each party in accordance with the agreement. So far the implementation of factoring agreement refers to article 1338 of the Civil Code following the principle of freedom to make a contract, and if there are problems arising from this institution, legal settlement is possible through a court or through arbitration. It depends on the agreement made by the parties involved. The results showed that the nature of the legal relationship between factor and client is the nature of the legal relationship in the form of a loan agreement, and the fact that the principle of balance does not apply to factoring agreements, this is due to the format and content of the agreement unilaterally determined by factoring , and cannot be negotiated again by the debtor. As a result, the debtor's position is very weak compared to the creditor's position. To realize the principle of balance requires efforts from the government in the form of laws governing the basic rules that must be considered by the parties who wish to enter into factoring agreements.How to cite item: Mochtar, D. (2019). Asas Keseimbangan dalam Pelaksanaan Perjanjian Anjak Piutang (Factoring). Jurnal Cakrawala Hukum, 10(2), 146-155. doi:https://doi.org/10.26905/idjch.v10i2.3558